FACTORS AFFECTING EARNINGS MANAGEMENT IN THE PLANTATION INDUSTRY IN INDONESIA DURING 2015-2019 - Maginta, Irianto; Lukman, Hendro (International Journal of Application on Economics and Business, 2023)
The objective of this research is to obtain empirical evidence about the effect of profitability, leverage, firm size, and liquidity on earnings management on plantation companies listed on the Indonesia Stock Exchange (IDX) during the years of 2015-2019. This research uses secondary data. This research is conducted with a sample of 62 plantation company data with the technique used in this study is purposive sampling. The research data was processed using Statistical Product and Service Solution program for Windows version 26 (SPSS version 26). The results of this research show that the leverage and firm size have a positive and influence on earnings management practices, while profitability and liquidity have no effect on earnings management. The implication of this research is that companies must communicate intensively with shareholders so that this does not occur or can reduce information asymmetry in carrying out earnings management. By maintaining good communication with shareholders, and maintain profitability, proper leverage ratio and liquidity as well as optimizing assets to earn profit, it is believed that the financial report information issued by the company does not involve earnings management practices so that it becomes a positive signal for investors which can ultimately increase stock prices and company value.